Conflict management and the value of emotions in organisations: Study of the internal customer versus the external customer - Paradinas Márquez, María del Carmen; Sánchez-González, Pilar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Based on the fact that companies obtain better results if their professional team is integrated and considers itself to be valued by its superiors and by the end client, this work analyses the value that Emotion Management can have in Business Conflict Management. To this end, a thorough bibliographical review of the concept and its application is carried out and the results obtained from quantitative research carried out in the Hotel Sector are shown. The results demonstrate the relevance of Emotions in any of the company’s relationships, both with internal and external clients.